Prolonged effect of a new O‐glycoPEGylated FVIII (N8‐GP) in a murine saphenous vein bleeding model. (4th June 2013) - Pastoft, A. E.; Ezban, M.; Tranholm, M.; Lykkesfeldt, J.; Lauritzen, B.
Summary: Prophylaxis in severe haemophilia significantly increases health‐related quality of life for patients, but the dosing frequency still constitutes a challenge. Thus, there is a need for new treatment options, utilizing compounds with longer duration of action, while still maintaining potency. The objective of this study was to evaluate the acute and prolonged effects of a new glycoPEGylated recombinant factor VIII (rFVIII) (N8‐GP) in a venous bleeding model in haemophilia A mice and to compare the efficacy and potency to turoctocog alfa (rFVIII). Following intravenous administration of turoctocog alfa or N8‐GP to normal and FVIII‐deficient mice, bleeding time and blood loss from a saphenous vein incision were evaluated in an acute dose–response study and a duration of action study. In the acute setting, N8‐GP dose dependently reduced the number and duration of bleeding episodes as well as blood loss compared to FVIII‐deficient mice, reaching statistical significance at doses as low as 5–10 U kg −1 . In the duration of action study, a significantly prolonged and maintained effect of N8‐GP was found for up to 48 h after dosing, whereas the effect of rFVIII was no longer present for any end‐points 24 h after dosing. Seventy‐two hours after dosing, no significant effect of either compound was found. This study shows a prolonged haemostatic effect of N8‐GP compared to rFVIII supporting other recent studies that N8‐GP may hold a potential to increase the quality of life for patients with haemophilia A by reducing dosing frequency.